NUMERICAL SIMULATION OF THE 2018 KRAKATAU TSUNAMI GENERATED BY FLANK COLLAPSE AND ASESSMENT OF TSUNAMI HEIGHT IN PANDEGLANG REGENCY - Latief, Hamzah; ISNAENI, KHOLILLAH YUDICIA; PUTRI, MUTIARA RACHMAT; FAIZIN, HAEKAL YUSRIL; DIASTOMO, HANIF; Anwar, Iwan Pramesti (Bulletin of Geology, 2023)
This study aims to reconstruct the tsunami event on December 22, 2018, due to the eruption of Anak Krakatau Volcano, which caused a flank collapse and generated an underwater landslide. Then this landslide caused a tsunami that impacted the coast of the Sunda Strait, especially on the coast of Pandeglang Regency. Based on satellite imagery, it is known that the landslide source came from the southwestern part of Anak Krakatau's wall moving down the former caldera wall of the 1883 Krakatau volcanic eruption. The mount grew again and was known as Anak Krakatau Volcano and appeared above sea level in 1929 and continued to grow. Subsequently, several eruptions spewed sediment deposits that had accumulated on the edges and foot of the mount. These sediments increased and became unstable, causing flank collapse and triggering underwater landslides. Several simulation scenarios have been carried out to obtain the best model that can represent the 2018 Anak Krakatau Tsunami with landslide parameters, namely: the volume of the landslide is 0.276 km3, the duration of propagation is 410 seconds, the inclination angle is 8.2°, and the length of the landslide trajectory is 3435 meters. The waveform generated as a tsunami source is in the form of wave peaks in the direction of the slide and wave valleys on the back of the slide. Furthermore, this wave propagated in all directions but primarily focused on the southwest, i.e., Panaitan Island and Pandeglang Regency. Tsunami simulations show that the tsunami reached: Panaitan Island and Pandeglang Regency at 58-60 minutes, Kota Agung (Lampung) at 42 minutes, and Ciwandan (Banten) at 46 minutes after the landslide with a tsunami height of 5.01m, 0.9 m, and 0.7 m respectively, with a maximum tsunami wave height of 18.6 m on Panaitan Island. Furthermore, it is known that five areas in Pandeglang Regency fall into the high tsunami hazard category with a tsunami height of more than 3 m, namely Panaitan Island, Ujungkulon District, Sumur, Panimbang, and Labuhan. By accurately knowing the distribution of tsunami height and estimating the time of arrival of the tsunami in the affected area and the inundation area, an early warning system and mitigation efforts can be planned, such as spatial planning and other actions. Key words: Anak Krakatau tsunami, numerical simulation, flank collapse, underwater landslide, Pandeglang Regency